Weighted H∞ consensus design for stochastic multi-agent systems subject to external disturbances and ADT switching topologies - Zhou, Jianping; Wang, Yang; Zheng, Xiao; Wang, Zhen; Shen, Hao (Nonlinear dynamics, 2019)
This paper is devoted to weighted H ∞ consensus design for continuous-time/discrete-time stochastic multi-agent systems with average dwell time (ADT) switching topologies and external disturbances via output feedback. By introducing a linear transformation, the closed-loop systems are changed into reduced-order systems and, at the same time, the issue of weighted H ∞ consensus design is transformed into a weighted H ∞ control problem. Then, Lyapunov conditions are established for the mean-square asymptotic stability and weighted H ∞ disturbance attenuation of the reduced-order systems. Based on them, two sufficient conditions are derived for the existence of desired output-feedback control protocols through the feasible solution of a series of linear matrix inequalities. Finally, two numerical examples are given to illustrate the effectiveness of the proposed results.